"Quantum Pendants" - the measurement of exposure to enhanced natural radioactivity. (15th June 2022) - Bonczyk, M.; Grygier, A.; Skubacz, K.
Highlights: "Scalar energy medallions" researched. The content of radionuclides was determined by gamma radiation spectrometry. Dose rate equivalents were determined by thermoluminescence dosimetry. The methods of X-ray diffraction (XRD) and X-ray fluorescence (XRF) were used. Abstract: Different methods of alternative medicine may cause increased exposure to humans due to natural radioactivity. "Scalar energy medallions", also known as "Quantum Pendants", were investigated in the present work. Such objects are easily available in herbal stores or online. The elevated concentration of natural radionuclides from thorium series ( 232 Th) and uranium series ( 238 U) were measured in such pendants. The measured concentrations reached values up to 49 100 Bq·kg −1 for 228 Ra, 51 600 Bq·kg −1 for 228 Th, and 7 900 Bq·kg −1 for 238 U and 226 Ra. Radioactive disequilibrium among radionuclides was observed and this fact may be indirect evidence of the industrial (not natural) origin of these materials. Therefore, such medallions should be considered as NORM (Naturally Occurring Radioactive Materials) or TENORM (Technologically Enhanced NORM). According to the suppliers, the medallions should be carried directly on the skin of the human chest. Therefore, elevated radiation exposure is expected. Due to the presence of natural radionuclides in elevated concentrations, a mixed radiation field is the source of exposure to humans. Such conditions imply some metrological difficulties due to complex types of radiation. The article presents a proposal for a measurement approach in such cases. The effective dose from beta, X and gamma radiation for the human body was measured with the use of body phantoms and Panasonic thermoluminescent (TL) dosimeters. Various combinations of TL detectors, radiation filters and calculation protocols were applied to determine the doses from beta, X and gamma radiation. The obtained total effective dose exceeds the limit for the general population – 1 mSv.